Epidemiological profile of pediatric heart failure in Brazil in the last 10 years (Research, Society and Development, 2025)
Introduction: Pediatric heart failure (HF), mainly associated with congenital and acquired heart disease, has high hospitalization and mortality rates, despite the lower incidence compared to adults. Objective: To analyze the epidemiological profile of hospitalizations for heart failure in children and adolescents in Brazil between 2015 and 2024. Methodology: Cross-sectional, descriptive study, based on data from the SUS Hospital Information System (DATASUS). Hospitalizations of patients aged 0 to 19 years with a diagnosis of HF (ICD-10: I50) were included. The analysis was performed in Microsoft Excel using descriptive statistics. Results: A total of 1,989,711 hospitalizations for HF were recorded in Brazil, of which 31,277 (1.6%) referred to the pediatric population. The age extremes (